Primary congenital bladder diverticula: Where does the ureter drain? - Antonio Macedo; Gilmar Garrone; Sérgio Leite Ottoni; Diego Estevam Oliveira; Geórgia Rubiane Meira do Rosário Souza; Marcela Leal da Cruz (Wolters Kluwer Medknow Publications, 2015)
Background: Primary congenital bladder diverticulum (PCBD) is related to a deficient detrusor layer allowing out-pouching of the bladder mucosa through the inadequate muscularis wall. We aimed to review our experience with symptomatic PCBD in order to correlate clinical findings with anatomical aspects and to present late outcome. Materials and Methods: We reviewed all patients operated in our institution since 2004. We evaluated the charts for complaints, radiological exams, method of treatment, complications and length of follow-up. Results: We treated 10 cases (11 renal units - [RU]), predominantly males (9/10), mean age at surgery of 5.3 years. All patients had significant urological complaints presenting either with antenatal hydronephrosis (4) or febrile urinary tract infection (5) and urinary retention in one. The ureter was found implanted inside the diverticulum in 8/11 RU. An extravesical psoas-hitch ureteroneocystostomy and diverticulum resection was performed in 10/11 cases, whereas 1 case was treated intravesically based on surgeon's preference without performing cystoscopy. Mean follow-up was 34.1 months (1-120) without complications. Conclusions: PCBD is an uncommon diagnosis and has a high probability of drainage inside the diverticulum (72.7%). We recommend the extravesical approach associated with diverticulectomy and ureteroneocystostomy as the preferred technique to treat this abnormality.